FORMULATION AND OPTIMIZATION OF HYDROXYUREA LOADED NANOSTRUCTURED LIPID CARRIERS USING DESIGN OF EXPERIMENT FOR THE EFFECTIVE TREATMENT OF OVARIAN CANCER - RAJENDRA, PRAHARSH KUMAR MANDADHI; BALAN, ANJALI PUTHUSSERIKKUNNU; SELVARAJ, JUBIE; JAWAHAR, NATARAJAN (International Journal of Applied Pharmaceutics, 2022)
Objective: Ovarian cancer is the most deadly cancer in women, ranking fourth among all fatal diseases in women. Conventional chemotherapy has its own plethora of challenges, such as side effects and disease relapse. Hydroxyurea is a type of anticancer drug that is commonly used to treat malignancies. This study aims to develop and optimize hydroxyurea nanostructured lipid carriers (NLCs) to improve the therapeutic index and reduce its side effects in the effective treatment of OC. Methods: NLCs were prepared by microemulsion technique. They were prepared and optimized using the design of experiment for particle size and drug entrapment efficiency. Particle size, polydispersity index, zeta potential, morphology, in vitro release, and stability were all examined in the optimized formulation. Results: The results showed that the particle size of the NLCs was in the range of 224 nm to 634 nm. The drug entrapment efficiency of the NLCs was in the range of 46.33 % to 70.43 %. The optimized NLCs had a particle size of 237 nm, a polydispersity index of 26.9%, and a zeta potential of-29.7 mV. These NLCs were spherical, showed in vitro drug release of 92.21% up to 48 h, and were found to be stable from the stability studies. Conclusion: This approach could be used as a better drug delivery platform to improve the drug's therapeutic index, reduce its side effects, and be feasible in the effective management of ovarian cancer.